GetReal: from efficacy in clinical trials to relative effectiveness in the real world. (7th July 2016) - Egger, Matthias; Moons, Karel G. M.; Fletcher, Christine; ,
Abstract : The GetReal consortium ("incorporating real‐life data into drug development") addresses the efficacy–effectiveness gap that opens between the data from well‐controlled randomized trials in selected patient groups submitted to regulators and the real‐world evidence on effectiveness and safety of drugs required by decision makers. Workpackage 4 of GetReal develops evidence synthesis and modelling approaches to generate the real‐world evidence. In this commentary, we discuss how questions change when moving from the well‐controlled randomized trial setting to real‐life medical practice, the evidence required to answer these questions, the populations to which estimates will be applicable to and the methods and data sources used to produce these estimates. We then introduce the methodological reviews written by GetReal authors and published in Research Synthesis Methods on network meta‐analysis, individual patient data meta‐analysis and mathematical modelling to predict drug effectiveness. The critical reviews of key methods are a good starting point for the ambitious programme of work GetReal has embarked on. The different strands of work under way in GetReal have great potential to contribute to making clinical trials research as relevant as it can be to patients, caregivers and policy makers. Copyright © 2016 John Wiley & Sons, Ltd.